Nociceptive Flexion Reflex Threshold in Chronic Pain Patients: A Needed Update for the Current Evidence. (August 2021) - Amiri, Mohammadreza; Esmaili, Hamid; Hamad, Abdul Hamid; Alavinia, Mohammad; Masani, Kei; Kumbhare, Dinesh
Abstract : Background: The nociceptive flexion reflex is a physiological, polysynaptic reflex triggered by a nociceptive stimulus activating a withdrawal response. In chronic musculoskeletal-related pain conditions, a decreased nociceptive flexion reflex threshold has been suggested as a possible recognition evidence for central sensitization that may cause alteration of central nervous system processing. Objective: The aim of the study was to systematically review reported comparisons of the nociceptive flexion reflex threshold in chronic pain patients and healthy individuals. Methods: Electronic databases covering studies published between January 1990 and December 2019 were systematically searched. After application of exclusion criteria, 20 studies including 28 trials were included in this review. For meta-analysis, we used a random-effects model and funnel plot for publication bias. This research was registered at PROSPERO (CRD42019140354). Results: Compared with healthy controls, standardized mean differences in nociceptive flexion reflex threshold were significantly lower in the total sample of chronic pain patients. Subgroup analysis indicated a homogenous decreased nociceptive flexion reflex threshold in studies reporting fibromyalgia, chronic pain, and joint pain while heterogeneity existed in other included pain conditions. Conclusions: A lower nociceptive flexion reflex threshold in patients experiencing chronic pain conditions may imply hyperexcitability in central nervous system processing. As a preliminary study, the findings would act as a basis for developing a methodology assisting current clinical practices Abstract : Supplemental digital content is available in the text.